(untitled) (Latakia University Journal -Medical Sciences Series, 2018)
إن الهدف الأساسي من هذه الدراسة هو تحليل جميع حالات انصباب التامور - ما عدا التالية لجراحة القلب - التي أدخلت إلى قسم الجراحة في مشفيي الأسد وتشرين الجامعيين في الفترة الزمنية الواقعة بين 2007-2016. تمت دراسة (63) حالة انصباب تامور، (38) مريضاً و(25) مريضة تتراوح أعمارهم بين (67-17) عاماً. كان أهم سببين لحدوث انصبابات التامور هما القصور الكلوي بنسبة 50.7% والخباثات بنسبة 34.9% وعلى رأسها سرطان الرئة الذي شكل 50% من مجموع الخباثات ونسبة 17.4% من مجموع المرضى العام. إجراء النافذة التامورية بفتح الصدر الأيسر كان هو الإجراء المفضل في مرضانا حيث بلغت نسبة إجرائه 68.2% وكانت نسبة النكس 4.6%، وكانت كمية الانصباب الناكس بسيطة جداً ولم تحتج إلى أي إجراء آخر. بزل التامور أجري عند 39.6% من المرضى وكانت نسبة النكس عالية جداً 80% لذلك ابتعدنا عن البزل كإجراء علاجي واقتصر دوره فقط عند المرضى غير المستقرين هيموديناميكياً أو كخطوة أولى وتحضير للنافذة التامورية. تم إجراء النافذة التامورية عبر مدخل تحت الرهابة بالتخدير الموضعي عند 11.11% من المرضى، وكانت نسبة النكس 28.6%، حيث اعتمدنا هذه الطريقة فقط في الحالات التي تكون فيها حالة المريض لا تسمح بإجراء المداخل الجراحية الأخرى أو أن عمر المريض قصير ومحدود. إجراء النافذة التامورية بتنظير الصدر المساعد عند 15.8% مع نسبة نكس 10% ونتائج واعدة. أمكن القيام أثناء إجراء النافذة التامورية بفتح الصدر أو التنظير ببعض الإجراءات التشخيصية والعلاجية الأخرى وذلك عند (19) مريضاً. لعب إجراء النافذة التامورية والإجراءات المرافقة دوراً هاماً في تشخيص الحالات مجهولة السبب بنسبة 23.8%. The main aim of this study is to analyze all cases of pericardial effusions - except post cardiac procedures - who were admitted to surgical department in Al-Assad and Tichreen University Hospital in the period between 2007-2016. (63) cases of Pericardial effusions were analyzed, (38) male and (25) female, their ages were ranging between (17-67) years. The most important two causes of pericardial effusions were renal failure (50.7%) and Malignancies (34.9%). lung cancer was the leading cause of Malignancies accounting 17.4% of whole cases and 50% of Malignancies. Pericardial window via left mini thoracotomy was the preferred procedure in our study. 68.2% of the patients under went this procedure, recurrent rate was 4.6%, and the amount of recurrent pericardial effusion was minimal and didn’t need any management. Pericardiocentesis was performed in 39.6% of our patients, recurrent rate was very high 80%, therefore it was abondend as a method of treatment and its role was considered only in hemodynamically unstable patients or as a first step of preparation for pericardial window. Pericardial window via subxyhoid under local anesthesia was performed in 11.11%; recurrent rate was high 28.6%.We consider this approach only in patients who are not fit to undergo other approaches or when the expected survival is very limited. Pericardial window via thoracoscopic approach was performed in 15.8% of our patients; recurrent rate was 10% with encouraging results. During performance of pericardial window via minithoracotomy or thoracoscopically we were able to perform in (19) patients many other diagnostic and therapeutic procedures such as pleurectomy, Biopsies from the lungs, mediastinal tumors, and mediastinal lymph nodes as well. The histopathological examination of the resected pericardial window and concurrent procedures played an important diagnostic role in 23.8% of idiopathic pericardial effusions.